Association of size‐fractionated indoor particulate matter and black carbon with heart rate variability in healthy elderly women in Beijing. (29th January 2018) - Dong, W.; Pan, L.; Li, H.; Miller, M. R.; Loh, M.; Wu, S.; Xu, J.; Yang, X.; Shan, J.; Chen, Y.; Deng, F.; Guo, X.
Abstract: Associations between size‐fractionated indoor particulate matter (PM) and black carbon (BC) and heart rate variability (HRV) and heart rate (HR) in elderly women remain unclear. Twenty‐nine healthy elderly women were measured for 24‐hour HRV/HR indices. Real‐time size‐fractionated indoor PM and BC were monitored on the same day and on the preceding day. Mixed‐effects models were applied to investigate the associations between pollutants and HRV/HR indices. Increases in size‐fractionated indoor PM were significantly associated with declines in power in the high‐frequency band (HF), power in the low‐frequency band (LF), and standard deviation of all NN intervals (SDNN). The largest decline in HF was 19% at 5‐minute moving average for an interquartile range (IQR) increase (24 μg/m 3 ) in PM0.5 . The results showed that smaller particles could lead to greater reductions in HRV indices. The reported associations were modified by body mass index (BMI): Declines in HF at 5‐minute average for an IQR increase in PM0.5 were 34.5% and 1.0% for overweight (BMI ≥25 kg/m 2 ) and normal‐weight (BMI <25 kg/m 2 ) participants, respectively. Moreover, negative associations between BC and HRV indices were found to be significant in overweight participants. Increases in size‐fractionated indoor PM and BC were associated with compromised cardiac autonomic function in healthy elderly women, especially overweight ones.